Evaluation of Echinacea purpurea Extracts as Immunostimulants: Impact on Macrophage Activation - Vieira, Sara F.; Gonçalves, Samuel M.; Gonçalves, Virgínia M. F.; Tiritan, Maria E.; Cunha, Cristina; Carvalho, Agostinho; Reis, Rui L.; Ferreira, Helena; Neves, Nuno M. (Planta Medica, 2024)
Echinacea purpurea has been traditionally used to strengthen the immune system. Therefore, herein, we investigated the potential of E. purpurea aqueous extracts (AEs) obtained from flowers (F), leaves (L), or roots (R) as an immune booster in human primary monocyte‐derived macrophages (hMDMs). Additionally, to identify the main class of compounds (phenolic/carboxylic acids vs. alkylamides) responsible for the bioactivity, the three AEs were fractioned by semi-preparative high-performance liquid chromatography (HPLC). The AEs and the isolated phenolic/carboxylic acidic fractions were not cytotoxic for hMDMs for all tested concentrations, as confirmed by the metabolic activity and DNA content assays. Moreover, AE drastically induced the production of the interleukin (IL)-6 and tumor necrosis factor (TNF)-α, with a minimal effect on IL-1β and prostaglandin E2 (PGE2), supporting their potential for macrophage activation. Interestingly, in the presence of the phenolic/carboxylic acidic fractions, this efficacy considerably decreased, suggesting a complementary effect between compounds. AE also triggered the phosphorylation of the extracellular signal-regulated kinase (ERK) 1/2 and p38 signaling pathways and upregulated the cyclooxygenase (COX)-2 expression in hMDMs. Overall, AE-F was demonstrated to be the most powerful immunostimulant extract that can be related to their higher number in identified bioactive compounds compared to AE-L and AE-R. These results highlight the efficiency of E. purpurea AE to enhance the function of a key cell type of the immune system and their potential as immunostimulant formulations for patients with a compromised immune system due to certain diseases (e.g., acquired immunodeficiencies) and treatments (e.g., chemotherapy).
Keywords: Echinacea purpurea; Asteraceae; phenolic/carboxylic acids; inflammation; signaling pathways; human primary macrophages